Evolution of the COPD Assessment Test Score during Chronic Obstructive Pulmonary Disease Exacerbations: Determinants and Prognostic Value - Darwin Feliz-Rodriguez; Santiago Zudaire; Carlos Carpio; Elizabet Martínez; Antonia Gómez-Mendieta; Ana Santiago; Rodolfo Alvarez-Sala; Francisco García-Río (Canadian Respiratory Journal)
BACKGROUND: An adequate evaluation of exacerbations is a primary objective in managing patients with chronic obstructive pulmonary disease (COPD).